Hak cipta dan perpustakaan - Ade Uswatun Sitorus (UIN Sumatera Utara, 2015)
The library as an institution with an important role in disseminating information and knowledge, also have an important role in copyright. The activities carried out in a library is very closely related to publishing, preserving, memilihara and care as well as the creation of a work, but it also supports the efforts of libraries penegakaan copyrights and the prevention of copyright infringement